Pediatric pharmaceutical interventions in self-medication: a descriptive study in community pharmacies - Sabrina Bedhomme; Hélène Vaillant-Roussel; Philippe Vorilhon; Elodie Lafarge; Bénédicte Pereton; Céline Prunet-Spano; Bruno Pereira; Brigitte Vennat; Chantal Savanovitch (BMC Primary Care, 2023)
Abstract Background The practice of self-medication is common but not without risk, especially for vulnerable populations such as the pediatric population. Community pharmacists have an important role of vigilance in dispensing drugs available without a medical prescription, with the possibility of carrying out a Pharmaceutical Intervention (PI) if necessary. The aim of our study was to characterize the Pediatric Pharmaceutical Interventions (PPIs) in self-medication carried out during a spontaneous request for a drug at the community pharmacy. Methods We conducted a descriptive study in 139 pharmacies in the Auvergne-Rhône-Alpes region (France). Data were collected from students under the supervision of internship masters in the pharmacy, using the validated GIPAMED (GrId for PhArmaceutical Self-MEDication interventions) notification grid, the first week of each month, from February to May for five years (2017 to 2021). Collected data were entered on a secure university platform. Results Of the 3,552 PIs collected, 8,3% (n = 286) were PPIs. Of these PPIs, 35% (n = 100) was generated by requests for optional prescription drugs contraindicated by the pathophysiological condition, 28.3% for drugs requiring a prescription and 20.6% for over the counter drugs not indicated by the symptomatology. Finally, 10% of requests required a referral for a medical consultation. Four Anatomical Therapeutic Chemical (ATC) classes accounted for more than 90% of the requests: respiratory system (39.5%), alimentary tract and metabolism (19.2%), nervous system (11.5%), and musculoskeletal system (10.8%). The most common drugs generating PPIs were: ibuprofen, oxomemazine and combination camphor/essential oils, mainly due to age-related or weight-related contraindication. Paracetamol also generated PPIs frequently, mainly due to problems with drug compliance and more precise infra-therapeutic doses. When these PPIs were dispensed, the pharmacist’s proposed solutions were accepted in 94.8% (n = 271) of the cases. Conclusions The community pharmacist has an important role in providing information about medicines and their correct use to patients. Our research shows that this attention benefits vulnerable populations, such as children, even for drugs that are widely used (e.g. paracetamol and non-steroidal anti-inflammatory drugs) or active substances for which there are age-related or weight-related contraindications (e.g. antitussives, camphor combinations).